Songs from St. Somewhere [compact disc] - Buffett, Jimmy (Mailboat Records, 2013)
Jimmy Buffet is back with his first new studio album since the 2009 release Buffet Hotel. Songs From St. Somewhere features the single Too Drunk to Karaoke with Toby Keith and a duet with Latin singer Fanny Lu.